Availability and Quality of Emergency Obstetric Care, an Alternative Strategy to Reduce Maternal Mortality: Experience of Tongji Hospital, Wuhan, China - Bangoura, Ismael Fatou; Hu, Jian; Gong, Xun; Wang, Xuanxuan; Wei, Jingjing; Zhang, Wenbin; Zhang, Xiang; Fang, Pengqian (Journal of Huazhong University of Science and Technology. Medical sciences, 2012)
The burden of maternal mortality (MM) and morbidity is especially high in Asia. However, China has made significant progress in reducing MM over the past two decades, and hence maternal death rate has declined considerably in last decade. To analyze availability and quality of emergency obstetric care (EmOC) received by women at Tongji Hospital, Wuhan, China, this study retrospectively analyzed various pregnancyrelated complications at the hospital from 2000 to 2009. Two baseline periods of equal length were used for the comparison of variables. A total of 11 223 obstetric complications leading to MM were identified on a total of 15 730 hospitalizations, either 71.35% of all activities. No maternal death was recorded. Mean age of women was 29.31 years with a wide range of 14-52 years. About 96.26% of women had higher levels of schooling, university degrees and above and received the education of secondary school or college. About 3.74% received primary education at period two (P2) from 2005 to 2009, which was significantly higher than that of period one (P1) from 2000 to 2004 (P0.05) (OR: 0.586; 95% CI: 0.442 to 0.776). About 65.69% were employed as skilled or professional workers at P2, which was significantly higher than that of P1 (P0.05). About 34.31% were unskilled workers at P2, which was significantly higher than that of P1 (P0.05). Caesarean section was performed for 9,930 women (88.48%) and the percentage of the procedure increased significantly from 19.25% at P1 to 69.23% at P2 (P0.05). We were led to conclude that, despite the progress, significant gaps in the performance of maternal health services between rural and urban areas remain. However, MM reduction can be achieved in China. Priorities must include, but not limited to the following: secondary healthcare development, health policy and management, strengthening primary healthcare services.